RELATIONSHIP BETWEEN RED BLOOD CELL AND PLATELET INDICES IN IRON DEFICIENCY ANEMIA - Rabbani, Sahar; Farooq, Muhammad; Naeem, Samina; Naeem, Muhammad Abdul; Uddin, Nasir; Zubair, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the correlation between the red blood cell and platelet indices in patients presenting with iron deficiency anemia at a tertiary care hospital of Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Department of Hematology, Combined Military Hospital Lahore, from Sep 2018 to Mar 2019. Methodology: The patients of age 1-70 years of either gender presenting with IDA were included in the study. The blood sample of patients were sent to laboratory to assess the red blood cell and platelet indices. SPSS-23 was used to analyze data. Results: Two hundred and seven patients fulfilling the inclusion criteria were included in this study. The mean age was 25.6 ±17.8years. Correlation was weak and insignificant between haemoglobin and packed cell volume (r=-0.385**, p<0.01), haemoglobin and mean cell volume (r=-0.225**, p<0.01), packed cell volume and mean cell haemoglobin (r =0.263**, p<0.01), & mean cell haemoglobin and mean platelet volume (r=0.143*, p<0.05). Correlation was moderate and significant between platelet distribution width and mean platelet volume (r=0.511**) & platelet distribution width and platelet large cell ratio (0.502**, p<0.01). Correlation was strong between mean platelet volume and platelet large cell ratio (r=0.759**, p<0.01). Conclusion: In conclusion, there was significant relation between red blood cell and platelets indices in iron deficiency anemia. Furthermore, haemoglobin and packed cell volume are weekly correlated, platelet distribution width and mean platelet volume are moderately correlated and mean platelet volume and platelet large cell ratio are strongly correlated.